Higher education affects accelerated cortical thinning in Alzheimer's disease: a 5-year preliminary longitudinal study. (16th September 2014) - Cho, Hanna; Jeon, Seun; Kim, Changsoo; Ye, Byoung Seok; Kim, Geon Ha; Noh, Young; Kim, Hee Jin; Yoon, Cindy W; Kim, Yeo Jin; Kim, Jung-Hyun; Park, Sang Eon; Kim, Sung Tae; et al.
ABSTRACT: Background: Epidemiological studies have reported that higher education (HE) is associated with a reduced risk of incident Alzheimer's disease (AD). However, after the clinical onset of AD, patients with HE levels show more rapid cognitive decline than patients with lower education (LE) levels. Although education level and cognition have been linked, there have been few longitudinal studies investigating the relationship between education level and cortical decline in patients with AD. The aim of this study was to compare the topography of cortical atrophy longitudinally between AD patients with HE (HE-AD) and AD patients with LE (LE-AD). Methods: We prospectively recruited 36 patients with early-stage AD and 14 normal controls. The patients were classified into two groups according to educational level, 23 HE-AD (>9 years) and 13 LE-AD (≤9 years). Results: As AD progressed over the 5-year longitudinal follow-ups, the HE-AD showed a significant group-by-time interaction in the right dorsolateral frontal and precuneus, and the left parahippocampal regions compared to the LE-AD. Conclusion: Our study reveals that the preliminary longitudinal effect of HE accelerates cortical atrophy in AD patients over time, which underlines the importance of education level for predicting prognosis.